PENGARUH PENGGUNAAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA ARAB KELAS II DI SDI INTEGRAL LUQMAN AL HAKIM 02 BATAM - nurhayati; Afrizawati; Wahyu Safitri (LP2M-Institut Agama Islam Abdullah Said Batam, 2021)
This research is a quantitative research conducted at SDI Integral Luqman Al Hakim 02 Batam with the aim of knowing how the effect of using flashcard media on student learning outcomes in class II Arabic subjects at SDI Integral Luqman Al Hakim 02 Batam. The population of this study were all students of class II, amounting to 76 students. Hypothesis test results show that the t-count value is 88.550 with a significant level (2-tailed) of 0.000 with df = (n-1) of 76 so that the t-table value is 1.890 at the significant level of 0.05. So tcount> ttable or 88.550> 1.980 then Ho is rejected and Ha is accepted, so there is an influence between the use of flashcard media on learning outcomes. Then analyzed by correlation analysis the results showed that the Sig. (2-tailed) of 0.000 <0.05 so that there is a correlation with a strong enough correlation level. The coefficient of determination (KD) is 20%. This means that flashcard media affects students' Arabic learning outcomes by 20% and 80% is influenced by other factors.